Pattern, Management, and Outcome of Poisoning in a Tertiary Care Hospital - Karki, Naresh; Singh, Vijay; Verma, Vinod Kumar (Journal of Lumbini Medical College, 2018)
Introduction: Poisoning is a significant global public health problem. The appropriate management of poisoning at emergency needs accurate assessment and immediate treatment. The immense chance for better outcomes occurs with early diagnosis and treatment. This study was conducted to assess pattern, management, and outcome of poisoning in tertiary care hospital. Methods: An observational cross-sectional study was conducted in which records of patients with a diagnosis of poisoning over a period of four years were reviewed. Results: A total of 138 patients were included in the study. A majority (63%) of them were females. Most (67.4%) were managed by general or supportive measure only. Gastric lavage was done in 60% of total patients while 52.9% patients received activated charcoal. Pralidoxime and atropine was received by 51.1% of patients treated with specific antidote. All the antidotes were administered through intravenous route. Regarding outcome, 89.9% were completely recovered. Suicidal poisoning was significantly higher in married as compared to unmarried patients (p = 0.029). Similarly, there was a significant relationship between occupation of the patients and manner of poisoning (p = 0.003). Outcome of treatment had a significant association with the manner of poisoning (p < 0.001). Further analysis revealed that the patients who expired in the hospital were more likely to ingest poison accidentally. Conclusion: Suicidal poisoning is common and females are more susceptible. Insecticide and rodenticide are the commonly ingested poisons. Treatment outcome of poisoning cases is generally favorable. DOI: ttps://doi.org/10.22502/jlmc.v6i1.201